Disaster medicine and pandemic response: A novel curriculum to improve understanding of complex care delivery during the COVID‐19 pandemic. Issue 4 (7th November 2021) - Peterson, Todd; Wallace, Doug; Evans, Joel; Edwards, Andrew; Patel, Aashka; Willig, James; Lineback, Norman; Thompson, Linda
Abstract: Background: Despite a 2009 recommendation from the AMA that disaster medicine and public health response training should be implemented in medical schools, anywhere from 31% to 47% of medical education programs lack a formalized disaster medicine curriculum. A need for disaster medicine response training for University of Alabama medical students in an appropriately socially distanced format was identified during the COVID‐19 pandemic. Methods: Our emergency medicine faculty in collaboration with the Federal Emergency Management Agency Center for Disaster Preparedness (FEMA CDP) created and implemented a novel virtual disaster medicine and pandemic response course for third‐year medical students at the University of Alabama at Birmingham (UAB). The course was administered via a teleconferencing platform (Zoom, Zoom Video Communications, Inc.) in spring 2020 to more than 130 medical students. Results: Using pre‐ and postcourse surveys, we assessed a change in student confidence levels for their ability to explain topics covered in the course and their understanding of a chosen disaster. The students reported an average increase of 2.183 on a 5‐point scale, with a score of 5 representing "completely confident" and a score of 1 representing "not at all confident." This course established the feasibility of a virtual instructor–led training (VILT) format for disaster medicine education and provided a template for the delivery of over 300 courses to more than 4, 000 first responders and medical professionals through the FEMA CDP. Conclusions: Through collaboration with the FEMA CDP, our UAB faculty were able to successfully deliver a novel virtual disaster‐preparedness and response course. The course resulted in subjective improvement of students' content understanding while also establishing the feasibility and effectiveness of a VILT format that could be readily applied to future courses in undergraduate medical education and beyond.